A weighted version of the Mishou theorem - Laurinčikas, Antanas; Šiaučiūnas, Darius; Vadeikis, Gediminas (Mathematical Modelling and Analysis, 2021)
In 2007, H. Mishou obtained a joint universality theorem for the Riemann and Hurwitz zeta-functions ζ(s) and ζ(s,α) with transcendental parameter α on the approximation of a pair of analytic functions by shifts (ζ(s+iτ),ζ(s+iτ,α)), τ ∈R. In the paper, the Mishou theorem is generalized for the set of above shifts having a weighted positive lower density. Also, the case of a positive density is considered.